Quality Assurance & Accreditation Issues and Practices in Mid-West University, Nepal - Shahi , Sushil Kumar (Journal of Entrepreneurship & Management Studies, 2025)
Quality assurance and accreditation issues and practices have become the integral academic issue and practice in all higher education institutes of Nepal for quality academic, research and innovation based entrepreneurship education. Purpose of this study was to describe and analyze quality assurance and accreditation issues in twenty higher education institutes of Mid-West University to provide work integrated higher education service in Karnlai Province and different parts of the Nepal. The focus was on teaching, learning and evaluation, faculty development, research and extension services, infrastructure, learning resources, interface, interface quality, students support, leadership and governance, innovative practice and performance improvement. This study has been conducted by selecting Deans, head of HEIs and QAA associated faculty members of each HEI of Mid-West University as its respondents as they are the key responsible people to assure quality education service mechanism in line with UGC QAA system. The research method was quantitative model with survey design using descriptive analysis. The instruments used was online and off line structured and open-ended questionnaires. The census study method was used to design questionnaires for collecting information. Along with identifying solutions to the challenges relating to Mid-West University quality assurance and accreditation implementation, the study has identified policy implications and recommendations to help Nurturing Excellence in Higher Education Programs of UGC for its effective implementation within Mid-West university for ensuring quality higher education services in Nepal. Findings has shown poor and average in all indicators of teaching-learning, research, innovation, capacity development focusing on the conclusion that MU HEIs must work hard to implement QAA plan for offering quality and work-integrated higher education in the region.